Hubungan Asupan Karbohidrat Dan Lemak Dengan Kadar Profil Lipid Pada Pasien Jantung Koroner Rawat Jalan Di Rsud Dr. Moewardi Surakarta - Setyo Rini, Dwi Rahayu; , Dwi Sarbini, SST, M.Kes; , Elida Soviana, S.Gz., M.Gizi (2015)
Introduction : Coronary heart disease ( CHD ) is a condition due to the narrowing , blockage or abnormalities of the coronary arteries . Narrowing or blockages can stop blood flow to the muscle that is characterized by pain . Some of the factors that cause CHD among other things food intake , diabetes mellitus , obesity , alcohol consumption , smoking, stress , physical activity , age and gender . Increased levels of blood lipids profile also affects the occurrence of coronary heart disease . Increased levels of lipid profile may be due to food intake among the intake of carbohydrates and fats . Objective : To determine the relationship of carbohydrate and fat intake with levels of lipid profiles in patients with coronary heart disease outpatients at Hospital Dr. Moewardi Surakarta . Research Methot : This research method using observational study design with cross sectional design peneliatian . Sampling by means of consecutive sampling can be the subject of study in 24 patients with coronary heart disease . Collecting data for carbohydrate and fat intake using recal 24 hours times 4 days , whereas the levels of lipid profiles obtained from medical records of patients . The relationship test performed using Pearson correlation test . Results : The percentage of normal carbohydrate intake is 58.3 % and the percentage of fat intake is 62.5 % less . While the percentage of normal cholesterol levels and percentage 95.8 % 62.5 % triglyceride levels normal . Conclusion : There is no relationship between intake of carbohydrates with high levels of lipid profiles , it can be seen from the value of p = 0.945 total cholesterol ( p ≥ 0.05 ) and p = 0.255 triglycerides ( p ≥ 0.05 ) . There is no relationship between fat intake with levels of lipid profiles , it can be seen from the value of p = 0.257 total cholesterol ( p ≥ 0.05 ) p = 0 , 976 ( p ≥ 0.05 ) .